1973
DOI: 10.1104/pp.52.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Separated Leaf Cells

Abstract: Separated mesophyll cells from cotton (Gossypium hirsutum var. Stoneville 1613 Glandless) were isolated with pectinase and mechanical agitation. The separated cells had rates of light-dependent C02 fixation between 50 to 100 umoles COa per mg chlorophyll per hour. The presence of Ca'+ in the incubation medium did not significantly affect the type of photosynthetic products formed, but 2 mM Cae+ did cause a 50% decrease in the appearance of photosynthetic products in the incubation medium. The movement of all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 6 publications
3
20
0
Order By: Relevance
“…EDTA apparently does not completely remove the callose plug once it forms (13). Other researchers have suggested that Ca2' also reduces the permeability of the plasma membrane (1,18,22). In this study, we suggest that Ca2+ reduced sugar efflux due to both a reduction of the permeability of the plasmalemma and the stimulation of sieve element plugging.…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…EDTA apparently does not completely remove the callose plug once it forms (13). Other researchers have suggested that Ca2' also reduces the permeability of the plasma membrane (1,18,22). In this study, we suggest that Ca2+ reduced sugar efflux due to both a reduction of the permeability of the plasmalemma and the stimulation of sieve element plugging.…”
mentioning
confidence: 47%
“…Calcium inhibits passive efflux of sugars from plant cells and its role in the maintenance of membrane structure and semipermeability has been demonstrated in several systems (1,18,22). Thorne and Rainbird (22) demonstrated that chelation of divalent cations, especially Ca2 , from the plasmalemma by EGTA or EDTA caused rapid leakage of "'C-assimilates from the seed coat.…”
mentioning
confidence: 99%
“…Present plant cell isolation procedures (6,12,19,21) are not entirely satisfactory in that they require a high osmotic concentration, and 1 to 3 hr are required for high cell yields. A method is described here for the rapid isolation, in high yield, of photosynthetically active mesophyll cells from soybean in the presence of a physiological concentration of osmoticum.…”
Section: Introductionmentioning
confidence: 99%
“…Each flask also contained 0.1 ml of the radioactive substrate making a final volume of 2.6 ml. This' method of cell isolation was a modification of previously described methods (7,10,17) and identical to that previously used (1).The assay methods for the processes studied were also essentially the same as previously described (1). After the appropriate radioactive substrate was added to the cell preparation, the flasks were stopped and placed in a 25 C shaking water bath illuminated from above with fluorescent lamps with an intensity of 4,300 lux at the level of the flasks.…”
mentioning
confidence: 99%
“…Each flask also contained 0.1 ml of the radioactive substrate making a final volume of 2.6 ml. This' method of cell isolation was a modification of previously described methods (7,10,17) and identical to that previously used (1).…”
mentioning
confidence: 99%